Clinical-pathological features and survival in young women with cervical cancer: a retrospective analysis from the Instituto Nacional de Enfermedades Neoplásicas - Rossana Ruiz; Mariana Serrano; Eloy F. Ruiz; Raul Mantilla; Natalia Valdivieso; Mivael Olivera; Manuel Alvarez; Luis Mas; Henry L. Gomez (Revista Peruana de Medicina Experimental y Salud Pública, 2017)
Objective. To determine the clinical and histological characteristics and prognostic factors of cervical cancer (CC) in young Peruvian patients. Materials and methods. Retrospective analysis of patients younger than 35 years old diagnosed with CC between 2008 and 2012 in the Instituto Nacional de Enfermedades Neoplásicas. Results. 449 patients had epithelial neoplasms. The main histological types were: squamous cell carcinoma (84.9%), adenocarcinoma (11.0%) and adenosquamous carcinoma (2.4%). The average tumor size was 4.98 cm. Anemia (55.7%), elevated creatinine (21.2%) and hydronephrosis (13.8%) were also identified. 82.3% of the patients presented locally advanced disease. Stages IIB (47.4%) and IIIB (25.8%) were the most common. Overall 5-year survival was 59.5% (I, 90.9%; II, 57.5%; III, 42.7% and IV, 13.3%). Elevated creatinine, anemia, tumor size, parametrial involvement and hydronephrosis were factors that affected survival. No significant relation was found between histological type and survival. The presence of anemia (adjusted hazard ratio [aHR]: 2.5; 95% confidence interval [CI 95%]: 1.6-4.0) and hydronephrosis (aHR: 1.6; CI 95%: 1.0-4.0) were independently associated with survival; likewise, the parametrial commitment with (aHR: 3.3; CI 95%: 1.5-7.2) or without (aRH: 2.6; CI 95%: 1.3-5.3) extension to the pelvic bone. Conclusions. Cervical cancer in young Peruvians is diagnosed in advanced stages. Overall survival in each stage is similar to the reported in older patients. The importance of conventional prognosisrelated factors was confirmed. Anemia was an important independent prognostic factor requiring further investigations.